Development and experiment of L-band SAR for ranging and imaging target - Kim, Kyeong Rok; Ryu, Sang Burm; Lee, Hyeon Cheol; Lee, Sang Gyu; Kim, Jae Hyun (International Geoscience and Remote Sensing Symposium (IGARSS), 2018)
A synthetic aperture radar (SAR) is globally studied in various purposes. Especially, the SAR applications such as image processing and image application have been dealt with several papers. However, it is hard to approach for student researcher a development of the SAR system. In this paper, we design and develop an L-band SAR system which has a small and modular structure. The SAR system consists of a chirp signal generator, an RF transmitter, an RF receiver, and a data recorder. We have used FPGA board for making the chirp signal generator and the data recorder to program parameters, which are used to generate chirp pulse signal and observed sample data. In addition, we experiment a target distance detection and automobile based SAR to verify our L-band SAR system. The experimental results show that the distance of the SAR system from the target is measured and the observed area can be roughly imaged. Moreover, we study and develop persistently for completion of the L-band SAR system.
Keywords: AutoSAR; L-band; Outdoor experiment; Synthetic aperture radar; Target detection